Antifungal Activity of Eugenol Analogues: Influence of Different Substituents and Studies on Mechanism of Action - Carrasco, Héctor (2012)
Twenty one phenylpropanoids (including eugenol and safrole) and synthetic analogues, thirteen of them new compounds, were evaluated for antifungal properties, first with non-targeted assays against a panel of human opportunistic pathogenic fungi. Some structure-activity relationships could be observed, mainly related to the influence of an allyl substituent at C-4, an OH group at C-1 and an OCH3 at C-2 or the presence of one or two NO2 groups in different positions of the benzene ring. All active compounds were tested in a second panel of clinical isolates of C. albicans and non-albicans Candida spp., Cryptococcus neoformans and dermatophytes. The eugenol derivative 4-allyl-2-methoxy-5-nitrophenol (2) was the most active structure against all strains tested, and therefore it was submitted to targeted assays. These studies showed that the antifungal activity of 2 was not reversed in the presence of an osmotic support such as sorbitol, suggesting that it does not act by inhibiting the fungal cell wall synthesis or assembly. On the other hand, the Ergosterol Assay showed that 2 did not bind to the main sterol of the fungal membrane up to 250 µg mL−1. In contrast, a 22% of fungal membrane damage was observed at concentrations = 1 × MIC and 71% at 4× MIC, when 2 was tested in the Cellular Leakage assay. The comparison of log P and MICs for all compounds revealed that the antifungal activity of the eugenol analogues would not to be related to lipophilicity.